Urach – južnoslavenski prevoditeljski i izdavački projekt u doba reformacije - Jembrih, Alojz (Slavia Centralis, 2020)
Urach – južnoslovanski prevajalski in izdajateljski projekt v obdobju reformacijeUrach was an important project in the period of Reformation. Although it eventually had no lasting impact in the South Slavic area, where books were printed in Glagolitic, Cyrillic and Latin alphabet, it represents an interesting feature regarding culture, translation science and publishing. Much has been written so far about it, but at the 500th anniversary of Reformation it is discussed once more in the light of some new data.
Keywords: reformation; typography in 16th Century; Bible; Primož Trubar; Stipan Konzul; Ivan Ungnad; Urach